The incidence of mandibular premolars with more than one root canal in a Turkish population. - (:unkn) unknown (My University, 1992)
One hundred and eighty seven mandibular premolars taken from a Turkish population were examined in this study. The teeth were soaked in India ink and then decalcified, cleared and used in an in vitro study to determine the number of root canals and their types, the ramifications of root canals, the location of apical foraminae and the frequency of apical deltas. It was found that the incidence of more than one canal in mandibular premolars was 27.76%; that of finding two or three separate canals in the same root was 9.62% and that of having more than one canal at the apex was 23.49%.